2021
DOI: 10.1590/fst.06120
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of antioxidant activity and biochemical composition of four seaweeds, Rocky Bay of Abu Qir in Alexandria, Egypt

Abstract: The current study estimated the antioxidant activity and biochemical composition of four seaweeds; Toania atomaria (Phaeophyta), Padina pavonia (Phaeophyta), Jania rubens (Rhodophyta) and Corallina elongate (Rhodophyta). The highest total antioxidant activity was observed with ethanol extract of T. atomaria (44.6 ± 1.6 mg ascorbic acid equivalents/g crude extract). Among the four seaweeds, ethanol extract of T. atomaria has recorded the highest value in ferric reducing antioxidant power (FRAP) assay (32.3 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 71 publications
1
24
1
Order By: Relevance
“…Given that this species showed the highest DPPH antiradical-scavenging capacity, several processes should be evaluated and optimized to obtain the highest yield possible. El-Sheekh et al (2021) reported that the extraction yield of P. pavonica is doubled when using ethanol as an extraction solvent compared with methanol.…”
Section: Fucoxanthin Total Phenolic Content and Dpph Radical-scavenging Capacity Of Dictyotalesmentioning
confidence: 99%
“…Given that this species showed the highest DPPH antiradical-scavenging capacity, several processes should be evaluated and optimized to obtain the highest yield possible. El-Sheekh et al (2021) reported that the extraction yield of P. pavonica is doubled when using ethanol as an extraction solvent compared with methanol.…”
Section: Fucoxanthin Total Phenolic Content and Dpph Radical-scavenging Capacity Of Dictyotalesmentioning
confidence: 99%
“…It has been reported that brown seaweeds have higher antioxidant properties comparatively than red and green seaweeds [23]. Brown seaweeds contain one of the most abundant pigment carotenoid compounds, fucoxanthin, and are estimated to contain around 10% of total carotenoids found in nature [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In this study the use of conventional solid-liquid extraction processes with ethanol or water as solvents sought to obtain extracts with different compositions and bioactivities. Extraction yields were higher with water as reported in other studies with red seaweeds including Agarophyton vermiculophyllum (formerly Gracilaria vermiculophylla) [69][70][71]. However, the results obtained in the ethanolic fractions in terms of average yield are lower than those obtained by Chan et al [36] regarding Crassiphycus changii (formerly Gracilaria changii, 13.06 ± 1.14%).…”
Section: Discussionmentioning
confidence: 45%